High-intensity focused ultrasound ablation around the tubing - Siu, Jun Yang (2018)
High-intensity focused ultrasound (HIFU) has been emerging as an effective and noninvasive modality in cancer treatment with very promising clinical results. However, a small vessel in the focal region could be ruptured, which is an important concern for the safety of HIFU ablation. In this study, lesion formation in the polyacrylamide gel phantom embedded with different tubing (inner diameters of 0.76 mm and 3 mm) at varied flow speeds (17–339 cm/s) by HIFU ablation was photographically recorded. Produced lesions have decreased length (~30%) but slightly increased width (~6%) in comparison to that without the embedded tubing. Meanwhile, bubble activities during the exposures were measured by passive cavitation detection (PCD) at the varied pulse repetition frequency (PRF, 10–30 Hz) and duty cycle (DC, 10%-20%) of the HIFU bursts. High DC and low flow speed were found to produce stronger bubble cavitation whereas no significant influence of the PRF. In addition, high-speed photography illustrated that the rupture of tubing was produced consistently after the first HIFU burst within 20 ms and then multiple bubbles would penetrate into the intraluminal space of tubing through the rupture site by the acoustic radiation force. Alignment of HIFU focus to the anterior surface, middle, and posterior surface of tubing led to different characteristics of vessel rupture and bubble introduction. In summary, HIFU-induced vessel rupture is possible as shown in this phantom study; produced lesion sizes and shapes are dependent on the focus alignment to the tubing, flow speed, and tubing properties; and bubble cavitation and the formation liquid jet may be one of the major mechanisms of tubing rupture as shown in the high-speed photography.